Exploring Student Perceptions of Blended Learning: Flexibility, ICT Literacy, and the Preference for Traditional Classroom Learning - Agus Ruswandi; Riki Ruswandi; M Aditya Firdaus; Revita Yanuarsari; Hendi S Muchtar (STAI Hubbulwathan Duri, 2025)
Student participation remains a key challenge in blended learning (BL), particularly in the Faculty of Islamic Religion and Teacher Training and Education. Understanding students’ perceptions is essential to evaluate the effectiveness of BL and identify areas for enhancement. This study employed a quantitative, non-experimental survey design. Data were collected from 238 students at Universitas Islam Nusantara through an online questionnaire. Descriptive statistical methods were used to analyze the data and calculate mean scores across various dimensions of students’ perceptions. The findings indicate that students generally perceive blended learning positively, with an overall mean score of 3.45 on a 4-point scale. Flexibility was viewed favorably, while convenience received a moderate rating (mean score: 3.1). Students also reported high levels of ICT literacy, averaging 3.6. Despite these positive aspects, a notable proportion of students still preferred face-to-face learning, citing it as more effective and easier for active participation. The results suggest that while blended learning enhances flexibility and supports digital skill development, concerns about convenience and engagement persist. These findings highlight the need for improved instructional design and better support systems within BL environments. Blended learning is perceived as effective and beneficial, particularly in developing ICT literacy. However, to increase student participation and overall satisfaction, institutions should focus on improving the usability and interactivity of blended platforms, as well as providing targeted support to address learner preferences and challenges.